Invasive lumbricid earthworms in North America—Different life histories but common dispersal?. (13th December 2019) - Klein, Andreas; Eisenhauer, Nico; Schaefer, Ina
Abstract: Aim: Lumbricid earthworms are invasive across northern North America, causing notable changes in forest ecosystems. During their range expansion, they encountered harsher climatic conditions compared to their native ranges in short time ( 400 years). This study investigated if (a) dispersal barriers, (b) climatic selection or (c) anthropogenic activities, that is fishing bait disposal, structure the dispersal of free‐living earthworm populations. Location: North America, forest habitats along former Wisconsinan glaciation line. Taxon: Lumbricus terrestris, L. rubellus . Methods: Lumbricus terrestris and L. rubellus co‐occur in the same habitats but differ in ecology and use as fishing bait. Both species were sampled in five transects ranging from the east to the west coast of northern North America, including major dispersal barriers, three different climate zones, and bait shops near sampling locations. Genetic diversity and structure were compared between the two species, and the presence of free‐living bait shop genotypes was assessed using four markers (COI, 16S rDNA, 12S rDNA, and H3). Results: Populations of both species were genetically diverse with some geographic structure, which was more pronounced in L. terrestris than in L. rubellus . Common haplotypes were present in all regions, but locally restricted haplotypes also occurred. Furthermore, two distinct genetic clades of L. terrestris co‐occurred only in the two most distant transects (Alberta and Minnesota). Genotypes identical to bait individuals were omnipresent in field populations of L. terrestris . Main Conclusions: Genetic diversity was high in both species, and invasive populations represented a genetic subset of European earthworms. Geographic and climatic dispersal barriers affected the less mobile species, L. terrestris, resulting in differences in genetic structure between the two species. Our results indicate common long‐distance dispersal vectors and vectors affecting only L. terrestris . The roles of climate and anthropogenic activities are discussed, providing additional explanations of dispersal and new insights into establishment of invasive earthworm populations.